2013
DOI: 10.1097/icu.0b013e3283641b86
|View full text |Cite
|
Sign up to set email alerts
|

Update in pediatric optic neuritis

Abstract: A comprehensive understanding of pediatric optic neuritis and its management remains elusive. A randomized clinical trial would potentially increase our knowledge and benefit the afflicted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…Moreover, several studies have reported a possible link between NMO and systemic immune mediated diseases. NMO is an inflammatory disorder with ON and acute myelitis also affecting children 11,15 . ON may be the first presentation of a developing multiple sclerosis and NMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies have reported a possible link between NMO and systemic immune mediated diseases. NMO is an inflammatory disorder with ON and acute myelitis also affecting children 11,15 . ON may be the first presentation of a developing multiple sclerosis and NMO.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, a work-up with cranial and orbital MRI, lumbar puncture and CSF studies including oligoclonal band and IgG index, and if needed further investigations for spinal MRI and neuromyelitis optica (NMO) IgG should be performed 10,11 . ON has been reported in the past with other immune mediated disorders like Behcet's disease, Sjogren's syndrome, Takayasu arteritis and systemic lupus erythematosus 9,[11][12][13][14] . Those cases might support a probable relationship between autoimmune and autoinflamatory disorders and ON.…”
Section: Discussionmentioning
confidence: 99%
“…Typical optic neuritis, the most common form of optic neuritis, is often associated with systemic demyelinating disease. Optic neuritis in the pediatric age group represents a special group of individuals which often requires therapeutic interventions (Collinge and Sprunger 2013). Atypical presentations of optic neuritis may include significant vision loss, absence of pain, bilateral and simultaneous vision loss, or a lack of significant improvement within 2-3 weeks of disease onset (Dumitrascu 2014).…”
Section: Optic Neuritismentioning
confidence: 99%
“…A greater proportion of patients with severe and/or bilateral vision loss is also characteristic of pediatric optic neuritis (26,27). Children with optic neuritis tend to recover faster than adults and a higher percentage involve secondary causes than in adults (28).…”
Section: Corticosteroids In Pediatric Optic Neuritismentioning
confidence: 99%
“…Despite the lack of prospective clinical data in children to support its use, high-dose intravenous methylprednisolone is considered first-line treatment for pediatric optic neuritis by extension from the ONTT, as affected children often present with impairment of visual acuity severe enough to justify its use. Following IVCS, a prolonged oral corticosteroid taper over 2-6 weeks is common, as some experts believe there is an increased rate of relapse with early cessation of corticosteroids (27,29,30). One recent small retrospective study of 26 consecutive pediatric patients with optic neuritis treated for 3 days with intravenous methylprednisolone compared those treated with an additional two weeks of oral corticosteroids to those treated for more than two additional weeks.…”
Section: Corticosteroids In Pediatric Optic Neuritismentioning
confidence: 99%